A history of Christianity in Indonesia - Aritonang, Jan S.; Steenbrink, Karel A. (Studies in Christian Mission, 2008)
Indonesia is the home of the largest single Muslim community of the world. Its Christian community, about 10% of the population, has until now received no overall description in English. Through cooperation of 26 Indonesian and European scholars, Protestants and Catholics, a broad and balanced picture is given of its 24 million Christians. This book sketches the growth of Christianity during the Portuguese period (1511-1605), it presents a fair account of developments under the Dutch colonial administration (1605-1942) and is more elaborate for the period of the Indonesian Republic (since 1945). It emphasizes the regional differences in this huge country, because most Christians live outside the main island of Java. Muslim-Christian relations, as well as the tensions between foreign missionaries and local theology, receive special attention.